PENGARUH RISIKO KREDIT DAN LIKUIDITAS TERHADAP PROFITABILITAS PADA PT BANK PEMBANGUNAN DAERAH JAWA BARAT DAN BANTEN TBK - Rohaeni, Heni; Rudiansyah, Diki (EKSPANSI, 2017)
Abstract: The purpose of this study was to determine the effect of credit risk and liquidity to profitabiitas partially and simultaneously. Descriptive verification method used quantitative approach. Credit Risk Thitung for NPL amounted -1.959 negative sign and Ttabel of 0.740, then by comparison Thitumg and Ttabel obtained figures -1.180 <0.740 with significant value of 0.145> 0.05. It can be concluded that partial NPL but not significant effect on profitability in BJB Bank. Liquidity Thitung for liquidity amounted to 0.850 is positive and ttabel figures obtained 0.850 <0.740 and significant value of 0.475> 0.05 it can be concluded that partial liquidity no significant effect on profitability in the BJB Bank. Credit risk and liquidity to Profitability in simultan with the provisions of a significant level of a = 0.05 or 5% with the degree of freedom DF1 = k-1 and DF2 = nk where Ftable value by 6, 94. So the results obtained from the comparison Fhitung with Ftabel of 2.261> 6.94 can be inferred credit risk and liquidity no significant effect on the profitability of the significance level of 0.252> 0.05. Keywords: NPL, LDR and Profitabilitas